2014
DOI: 10.1371/journal.pone.0105516
|View full text |Cite
|
Sign up to set email alerts
|

Association of CVD Candidate Gene Polymorphisms with Ischemic Stroke and Cerebral Hemorrhage in Chinese Individuals

Abstract: BackgroundContribution of cardiovascular disease related genetic risk factors for stroke are not clearly defined. We performed a genetic association study to assess the association of 56 previously characterized gene variants in 34 candidate genes from cardiovascular disease related biological pathways with ischemic stroke and cerebral hemorrhage in a Chinese population.MethodsThere were 1280 stroke patients (1101 with ischemic stroke and 179 with cerebral hemorrhage) and 1380 controls in the study. The genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…And MTRR restore oxidized cobalamin(II) to CH 3 -cobalamin(III) in order to maintain the activity of MTR [ 17 ]. MTHFR C677T (rs1801133) is a common mutation of MTHFR and its suggested being an unfavorable factor for cardiovascular diseases [ 19 , 20 ]. Yilmaz et al showed that the C allele has a protective effect on blood lipid concentration and the T allele has a harmful effect when they are screening MTHFR C677T polymorphism in renal transplant patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…And MTRR restore oxidized cobalamin(II) to CH 3 -cobalamin(III) in order to maintain the activity of MTR [ 17 ]. MTHFR C677T (rs1801133) is a common mutation of MTHFR and its suggested being an unfavorable factor for cardiovascular diseases [ 19 , 20 ]. Yilmaz et al showed that the C allele has a protective effect on blood lipid concentration and the T allele has a harmful effect when they are screening MTHFR C677T polymorphism in renal transplant patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the CC genotype, the enzyme activity of the CT and TT genotypes is less than 35% and 70%, respectively (Frosst et al, 1995). The decreased enzyme activity eventually leads to the elevation of Hcy levels (Atadzhanov et al, 2013;Ou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For the MTHFR gene, the cytosine (C) to thymine (T) substitution at position 677 (rs1801133) in the gene encoding region is the most common SNP. This variation leads to the conversion from alanine to valine at amino acid 222 (Jadavji et al, 2015), and is correlated with decrease of thermal stability of MTHFR and subsequent decrease of enzyme activity (Atadzhanov et al, 2013;Ou et al, 2014). Compared to the CC genotype, the enzyme activity of the CT and TT genotypes is less than 35% and 70%, respectively (Frosst et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the CC genotype, the enzyme activity of the CT and TT genotypes is less than 35% and 70%, respectively (Frosst et al, 1995). The decreased enzyme activity eventually leads to the elevation of Hcy levels (Atadzhanov et al, 2013;Ou et al, 2014). In other words, the CT and TT genotypes are correlated with elevated Hcy levels through reducing the activity of MTHFR.…”
Section: Discussionmentioning
confidence: 99%
“…For the MTHFR gene, the cytosine (C) to thymine (T) substitution at position 677 ( rs1801133) in the gene encoding region is the most common SNP. This variation leads to the conversion from alanine to valine at amino acid 222 (Jadavji et al, 2015), and is correlated with decrease of thermal stability of MTHFR and subsequent decrease of enzyme activity (Atadzhanov et al, 2013;Ou et al, 2014). Compared to the CC genotype, the enzyme activity of the CT and TT genotypes is less than 35% and 70%, respectively (Frosst et al, 1995).…”
Section: Discussionmentioning
confidence: 99%